2023
DOI: 10.1177/07067437231164571
|View full text |Cite
|
Sign up to set email alerts
|

Competencies for Repetitive Transcranial Magnetic Stimulation in Postgraduate Medical Education: Expert Consensus Using a Modified Delphi Process

Abstract: Background Repetitive transcranial magnetic stimulation (rTMS) is recommended in Canadian guidelines as a first-line treatment for major depressive disorder. With the shift towards competency-based medical education, it remains unclear how to determine when a resident is considered competent in applying knowledge of rTMS to patient care. Given inconsistencies between postgraduate training programmes with regards to training requirements, defining competencies will improve the standard of care in rTMS delivery.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Institutions have explored the value of disseminating self-learning modules (SLM) on TMS for treatment-resistant depression, and found that SLMs could serve as effective primers for trainees prior to hands-on training ( 27 ). Finally, the modified Delphi process could be utilized to develop consensus in postgraduate ECT and TMS competencies ( 28 , 29 ).…”
Section: Introductionmentioning
confidence: 99%
“…Institutions have explored the value of disseminating self-learning modules (SLM) on TMS for treatment-resistant depression, and found that SLMs could serve as effective primers for trainees prior to hands-on training ( 27 ). Finally, the modified Delphi process could be utilized to develop consensus in postgraduate ECT and TMS competencies ( 28 , 29 ).…”
Section: Introductionmentioning
confidence: 99%